Enhancing the Speech Delivery Skills of Grade 12 Learners Through Target Public Speaking Workshop - El Chamberlain Abellana; Losel Mae S. Abellana; Florabel C. Lovido (Journal of Research in Education and Pedagogy, 2025)
This study evaluates the implementation of a speech training workshop designed to enhance public speaking skills among senior high school learners at Bukidnon National High School. Recognizing the critical importance of communication skills in academic and professional settings, the workshop was developed using techniques from the Toastmasters International Competent Communication handbook. It was grounded in Kolb’s (1984) experiential learning theory, which emphasizes learning as a cyclical process comprising concrete experience, reflective observation, abstract conceptualization, and active experimentation. These stages were integrated into the workshop structure to ensure learners actively engaged in meaningful, reflective, and practice-oriented activities. Participants underwent pre- and post-assessments to measure improvements across eight critical aspects of public speaking: content, organization, vocal clarity, vocal variety, language use, eye contact and body gestures, persuasiveness, and adherence to time. The pre-assessment results revealed participants’ fair performance, with a mean score of 2.6, categorized as “fair.” However, the post-assessment demonstrated significant progress, with a mean score of 4.0, classified as “very good.” Statistical analysis using paired sample t-tests confirmed the significance of these improvements (p<0.05), demonstrating the workshop’s effectiveness in developing public speaking competencies. In addition to quantitative data, qualitative insights were gathered through focus group discussions. These revealed that learners not only improved their technical skills but also developed greater confidence, reduced anxiety, and enhanced audience engagement. Participants particularly valued the experiential approach, which allowed them to practice speeches, receive feedback, and refine their techniques iteratively. Despite these successes, challenges remained, particularly in mastering impromptu speaking and achieving effective vocal variety. These were addressed through targeted activities, including real-time speech exercises and facilitator coaching. Overall, this research highlights the transformative potential of combining experiential learning theory with structured communication training. It provides valuable insights for educators seeking to foster critical communication skills among learners, which are essential for personal and professional success.